2017
DOI: 10.3168/jds.2016-12425
|View full text |Cite
|
Sign up to set email alerts
|

Effect of tea saponins on milk performance, milk fatty acids, and immune function in dairy cow

Abstract: This study investigated the effects of tea saponins (TSP) on milk performance, milk fatty acids, and blood immune function in dairy cows. A total of 20 early-lactation Holstein cows (days in milk = 66.4 ± 16.8 d; parity = 1.75 ± 0.91; and milk yield = 36.3 ± 7.32 kg/d; mean ± standard deviation) were randomly divided into 4 homogeneous treatment groups, with TSP added at 0, 20, 30, and 40 g/d per head, respectively. All cows had 2 wk of adaptation and 6 wk of treatments. Feed, milk, and blood were sampled and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 41 publications
0
25
0
Order By: Relevance
“…Ilsley et al (2003) reported that supplementing a diet with 250 mg/kg Quillaja saponin increased dry matter and crude protein digestibility of the sows. According to Hu et al (2006) and Wang et al (2017), triterpenoid saponins may inhibit growth performance at high doses and promote growth performance at low doses. Indeed, Ilsley et al (2005) noted that a diet containing 750 mg/kg Quillaja saponin did not affect the growth performance of pigs but feeding the pigs with a diet supplemented with 1300 mg/kg Quillaja saponin negatively affected their growth performance.…”
Section: Introductionmentioning
confidence: 99%
“…Ilsley et al (2003) reported that supplementing a diet with 250 mg/kg Quillaja saponin increased dry matter and crude protein digestibility of the sows. According to Hu et al (2006) and Wang et al (2017), triterpenoid saponins may inhibit growth performance at high doses and promote growth performance at low doses. Indeed, Ilsley et al (2005) noted that a diet containing 750 mg/kg Quillaja saponin did not affect the growth performance of pigs but feeding the pigs with a diet supplemented with 1300 mg/kg Quillaja saponin negatively affected their growth performance.…”
Section: Introductionmentioning
confidence: 99%
“…Plant secondary metabolites, such as flavonoids and saponins, have anti-inflammatory, antioxidant, and antimicrobial properties in humans or ruminants (Harborne and Williams, 2000;Wang et al, 2017a) and mulberry could alleviate the severity of diarrhea in an experimental model of diarrhea in mice and rats (Di Carlo et al, 1993). Mulberry (Morus alba L.) leaves may be a potential source of natural antioxidants due to their marked antioxidant activity (Arabshahi-Delouee and Urooj, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Saponins are another bioactive component in tea brewing and its extract, and usually exhibit antioxidant, immuno-regulatory, anticancer, and cardiovascular-protective effects [11,[53][54][55]. Moreover, tea saponins are generally regarded as safe compounds that have anti-fungal and insecticidal properties and are widely used in the field of agriculture and food industry [56,57].…”
Section: Saponinsmentioning
confidence: 99%
“…Tea and its bioactive components also exhibit systematic and peripheral immuno-regulatory activities in vivo. Wang et al reported that the immunity of dairy cows was improved after a 6-week administration of tea saponins (0, 20, 30, and 40 g/d) [11]. Sharma et al declared that EGCG (100 mg/kg BW) from green tea enhanced the systemic immunity in aged male Swiss albino mice by improving the cellular immune response and simultaneously alleviating the antibody response aided by increased adrenal dehydroepiandrosterone [99].…”
Section: Immuno-regulative Activity In Vivomentioning
confidence: 99%
See 1 more Smart Citation